Unearthing Shifts in Microbial Communities Across a Soil Disturbance Gradient - Seitz, Taylor J.; Schütte, Ursel M. E.; Drown, Devin M. (Frontiers in Microbiology, 2022)
Permafrost, an important source of soil disturbance, is particularly vulnerable to climate change in Alaska where 85% of the land is underlain with discontinuous permafrost. Boreal forests, home to plants integral to subsistence diets of many Alaska Native communities, are not immune to the effects of climate change. Soil disturbance events such as permafrost thaw, wildfires, and land use change can influence abiotic conditions which can then affect active layer soil microbial communities. In a previous study, we found negative effects on boreal plants inoculated with microbes impacted by soil disturbance compared to plants inoculated with microbes from undisturbed soils. Here, we identify key shifts in microbial communities altered by soil disturbance using 16S rRNA gene sequencing and make connections between microbial community changes and previously observed plant growth. Additionally, we identify further community shifts in potential functional mechanisms using long read metagenomics. Across a soil disturbance gradient, microbial communities differ significantly based on the level of soil disturbance. Consistent with the earlier study, the family Acidobacteriaceae, which consists of known plant growth promoters, was abundant in undisturbed soil, but practically absent in most disturbed soil. In contrast, Comamonadaceae, a family with known agricultural pathogens, was overrepresented in most disturbed soil communities compared to undisturbed. Within our metagenomic data, we found that soil disturbance level is associated with differences in microbial community function, including mechanisms potentially involved in plant pathogenicity. These results indicate that a decrease in plant growth can be linked to changes in the microbial community and functional composition driven by soil disturbance and climate change. Together these results build a genomic understanding of how shifting soil microbiomes may affect plant productivity and ecosystem health as the Arctic warms.